2014
DOI: 10.1089/met.2013.0118
|View full text |Cite
|
Sign up to set email alerts
|

Serum Resistin Levels Are Associated with Adiposity and Insulin Sensitivity in Obese Hispanic Subjects

Abstract: Background and Aims: Resistin is involved in the development of obesity and insulin resistance (IR) in mice and may play a similar role in humans through mechanisms that remain unresolved. The objective of this study was to characterize the relationship between resistin levels in obese subjects with and without IR among Hispanic subjects. Material and Methods: A cross-sectional study was performed on 117 nondiabetic Hispanic subjects of both genders that were allocated into three study groups: A control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 41 publications
2
35
0
3
Order By: Relevance
“…Obese phenotype has been associated with a reduction in the anti-inflammatory and a boost in the pro-inflammatory adipokines. Our previous reports suggest interleukin 1β (IL1β) 22 , resistin 23 and TNFα 24 to play an important role in the development of obesity, islet dysfunction and decreased insulin secretion. On the contrary, adiponectin 2 , omentin-1 25 , melatonin 26 and vaspin 27 are known to enhance insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Obese phenotype has been associated with a reduction in the anti-inflammatory and a boost in the pro-inflammatory adipokines. Our previous reports suggest interleukin 1β (IL1β) 22 , resistin 23 and TNFα 24 to play an important role in the development of obesity, islet dysfunction and decreased insulin secretion. On the contrary, adiponectin 2 , omentin-1 25 , melatonin 26 and vaspin 27 are known to enhance insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Diet‐induced obesity impairs NPY/AGRP neuronal responsiveness to ghrelin (Briggs, Enriori, Lemus, Cowley, & Andrews, ). Higher resistin levels are associated with higher adiposity and lower insulin sensitivity (Nieva‐Vazquez, Pérez‐Fuentes, Torres‐Rasgado, López‐López, & Romero, ). The current study has demonstrated a decrease in the protein IGF‐1 levels (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PRL reduction were stated in the two survey; one of them evaluated the effects of 12-months physical activity in patients with DMT2 [50] and the other assessed the effects of 16 weeks of resistance training in older postmenopausal women [24]. Notably, increased resistin levels has been reported in study on obese mice [51] and also it should be noted that; resistin levels are described higher in men than in women [52].…”
Section: Discussionmentioning
confidence: 99%